2022
DOI: 10.7554/elife.63296
|View full text |Cite
|
Sign up to set email alerts
|

Bronchus-associated macrophages efficiently capture and present soluble inhaled antigens and are capable of local Th2 cell activation

Abstract: In allergic asthma, allergen inhalation leads to local Th2 cell activation and peribronchial inflammation. However, the mechanisms for local antigen capture and presentation remain unclear. By two-photon microscopy of the mouse lung, we established that soluble antigens in the bronchial airway lumen were efficiently captured and presented by a population of CD11c+ interstitial macrophages with high CX3CR1-GFP and MHC class II expression. We refer to these cells as Bronchus-Associated Macrophages (BAMs) based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 87 publications
2
18
0
Order By: Relevance
“…Mac1 ( FABP4 ) and quiesMacs (defined by overall lower gene expression) were enriched for canonical Macs ( MARCO , MSR1 , and VSIG4 ) and lipid metabolism genes ( FABP4 and APOE ), consistent with previously described luminal Macs ( 16 , 25 , 51 ). Mac2 ( A2M ) had high expression of complement family genes ( C1QA , C1QB and C1QC ) and lower relative expression of canonical Mac markers, reminiscent of airway-associated Macs (AAMs) recently characterized in mice ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mac1 ( FABP4 ) and quiesMacs (defined by overall lower gene expression) were enriched for canonical Macs ( MARCO , MSR1 , and VSIG4 ) and lipid metabolism genes ( FABP4 and APOE ), consistent with previously described luminal Macs ( 16 , 25 , 51 ). Mac2 ( A2M ) had high expression of complement family genes ( C1QA , C1QB and C1QC ) and lower relative expression of canonical Mac markers, reminiscent of airway-associated Macs (AAMs) recently characterized in mice ( 57 , 58 ).…”
Section: Resultsmentioning
confidence: 99%
“…moMacs after 21 days in coculture acquired a transcriptional profile similar to that of Mac2 ( A2M ) and were highly enriched for complement genes ( C1QA , C1QB , and C1QC ) and MERTK . Murine AAMs, which are transcriptionally similar to Mac2 ( A2M ), are replenished by CCR2 + monocytes, integrate in the airway epithelium, and exhibit dendriform morphology ( 57 , 58 ). We therefore performed immunofluorescence staining of day 21 cocultures and confirmed that these cells colocalize with the epithelial basal layer, acquire dendritic projections, and express C1Q and MERTK (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, clearly more detailed analyses will be needed to further explore on this issue und clarify its relevance in the differences observed between OVA- and HDM-AAI. Further, resident macrophages associated to the bronchi (BAM) have recently been described to capture and present antigens and activate Th2 cells in the lung ( 40 ). These BAM are CD11c + IM characterized by high CX3CR1 and MHCII expression.…”
Section: Discussionmentioning
confidence: 99%
“…Th2s provide concomitant support for ILC2s in the form of IL-2 144 , solidifying the mutualistic relationship between these cell types within the tissues. An interesting preprint recently found bronchus-associated macrophages interact with effector Th2s in the lung and enhance effector cytokine production from T cells in vitro 165 . Basophils have also been implicated in supporting Th2 responses in the tissues.…”
Section: Introductionmentioning
confidence: 99%